Manpower and Service Quality of Fast-Food Restaurant: KFC Restaurant - Ng Hee Song; Nikolas F Wuryaningrat; Alia Farhanim binti Mohd Ibrahim; Daisy Mui Hung Kee; Alia Izzani binti Md Nasir; Alice Law San San; Alice Rebecca A/P Edward George; Rivanti Kawung (Journal of The Community Development in Asia, 2022)
A fast-food restaurant, commonly known as a quick-service restaurant (QSR) in the business, is a type of eatery that specializes in fast food and offers limited table service. In the food sector, customer satisfaction and good feedback are the most important thing. Each company also has its main power source to maintain business. The goal of this study is to find how service quality can affect customer satisfaction. This study used a service quality model which is Servqual as a guide in determining customer satisfaction. The researchers chose Kentucky Fried Chicken (KFC) Restaurant in Malaysia for this case study. KFC Restaurant has many competitors in the fast-food restaurant industry. The solution to these issues is to develop ways to increase service quality and customer satisfaction.